Evaluation of acromion morphology and subacromial distance in patients with shoulder pain - Bahtiyar, Banu; Açıkgöz, A. Kürşad; Bozkır, Memduha Gülhal (Journal of Surgery and Medicine, 2022)
Background/Aim: Acromion morphology is not always considered when examining pathologies that may cause shoulder pain in patients who are undergoing physical therapy. However, acromion morphology and the changes caused by these morphological variations in the subacromial distance may cause serious shoulder problems during physical therapy. In this study, the effects of acromion morphology and subacromial distance measurements on shoulder pain were investigated, and the effects of various factors on acromion types were examined. Methods: Our study was a cross-sectional design, and in total, 240 patients had shoulder magnetic resonance images (MRIs) were included in the study. The study included patients with shoulder pain persisting for at least eight weeks and excluded patients with a history of fractures, peripheral nerve damage, osteogenesis imperfecta, and severe osteoporosis. Acromial morphology and subacromial distance were examined on MRIs. Acromial morphology was examined in four subgroups according to the classification by Vanarthos and Monu (1995). Furthermore, the patients were divided into three age groups (18–30, 31–45, and 46–60), and acromion types were examined based on these age groups. In addition, patients’ demographic data were collected, and patients were questioned about painful extremities, dominant extremity, and pain status based on the visual analogue scale (VAS). Results: Subacromial space was measured by determining acromion types using MRIs, and mean subacromial distance was 7.91 mm. Acromion types had significant differences in terms of subacromial distance values (P < 0.001). Pairwise comparisons revealed that the subacromial distance values of Type 3 patients were lower than that of Types 1, 2, and 4 patients (P < 0.001, P = 0.001, and P < 0.001, respectively). Conclusion: The study results revealed that injury of the rotator cuff muscles may occur more frequently in Type 3 acromion than in other acromion types because of the low subacromial distance value. Acromion types, especially the subacromial distance, must be considered in patients with shoulder pain.